National mitigation potential from natural climate solutions in the tropics. (16th March 2020) - Griscom, Bronson W.; Busch, Jonah; Cook-Patton, Susan C.; Ellis, Peter W.; Funk, Jason; Leavitt, Sara M.; Lomax, Guy; Turner, Will R.; Chapman, Melissa; Engelmann, Jens; Gurwick, Noel P.; Landis, Emily; et al.
Abstract : Better land stewardship is needed to achieve the Paris Agreement's temperature goal, particularly in the tropics, where greenhouse gas emissions from the destruction of ecosystems are largest, and where the potential for additional land carbon storage is greatest. As countries enhance their nationally determined contributions (NDCs) to the Paris Agreement, confusion persists about the potential contribution of better land stewardship to meeting the Agreement's goal to hold global warming below 2°C. We assess cost-effective tropical country-level potential of natural climate solutions (NCS)—protection, improved management and restoration of ecosystems—to deliver climate mitigation linked with sustainable development goals (SDGs). We identify groups of countries with distinctive NCS portfolios, and we explore factors (governance, financial capacity) influencing the feasibility of unlocking national NCS potential. Cost-effective tropical NCS offers globally significant climate mitigation in the coming decades (6.56 Pg CO2 e yr −1 at less than 100 US$ per Mg CO2 e). In half of the tropical countries, cost-effective NCS could mitigate over half of national emissions. In more than a quarter of tropical countries, cost-effective NCS potential is greater than national emissions. We identify countries where, with international financing and political will, NCS can cost-effectively deliver the majority of enhanced NDCs while transforming national economies and contributing to SDGs. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'.